The formation kinetic of mechanochemical synthesized perovskites - Kozma Gábor (Proceedings of the International Symposium on Analytical and Environmental Problems, 2021)
In this study, we aimed to achieve mechanochemical perovskite synthesis and to quantify the energy used during milling (Eb - impact energy and Ecum - cumulative energy) and to describe the relationship between them. For mechanochemical treatment a Fritsch Pulverisette-6 type planetary ball mill was used. As a model compound the widely used barium-titanate (BaTiO3) was chosen, which was produced by the reaction of barium-oxide (BaO) and titanate-dioxide (TiO2). The aim was to track the formation of BaTiO3 and to determine the minimum milling energies required for its production. Three important parameters were considered for the calculation of energy values: the material of the milling vials and balls, the number of balls and the speed of rotation. The transformation was tracked by X-ray diffraction (XRD) measurement, and the applied energy was determined using the Burgio-Rojac energy model. Our goal was to draw conclusions that can be used to predetermine optimal milling parameters in the production of other perovskite structured materials. The hypothesis was verified by the mechanochemical synthesis of zinc-titanate (ZnTiO3) which was produced by the reaction of zinc-oxide (ZnO) and TiO2.